(untitled) (Mongolian Journal of Astronomy and Geophysics, 2025)
A massless point is considered to move under the influence of the gravitational attraction of a central body and a perturbing acceleration P. The vector P remains constant in a reference frame whose axes are aligned with the velocity vector, the normal to the orbital plane, and the vector of the orbital plane’s area. In this reference frame, the shift norm of the celestial body’s orbit is determined. For celestial bodies with diameters less than 45 meters, since ρ₃ exceeds the Earth’s radius, it is possible to achieve an orbital deflection within one month. In contrast, for celestial bodies with diameters up to 100 meters, an orbital deviation can be achieved within one year.